Evaluation of intervention measures at different stages of the production chain in Argentinian exporting abattoirs - Brusa, Victoria; Restovich, Viviana; Signorini, Marcelo; Pugin, Daniela; Galli, Lucía; Ruíz Díaz, Vanesa; Arias, Romina; Leotta, Gerardo Anibal (Sage Publications, 2019)
Antimicrobial treatments could help to decrease the transmission of microorganisms to beef carcasses and abattoir environments. The aim of this study was to evaluate the effectiveness of interventions in reducing Shiga toxin genes (stx1 and stx2) presence in a commercial abattoir. Intervention measures included the application of electrolytically generated hypochlorous acid to steer pens (experiment 1), chlorinated water, electrolytically generated hypochlorous acid, and isoclor to steer pens (experiment 2), electrolytically generated hypochlorous acid to knocking pens (experiment 3), and aqueous ozone and electrolytically generated hypochlorous acid onto beef carcasses (experiment 4). Detection of stx in samples was performed with BAX® System Real-Time PCR Assay. Our results showed that treatment with pressurized electrolytically generated hypochlorous acid and isoclor were effective to reduce stx presence from hides on steer pens. Although there is no single strategy to ensure the reduction of stx presence in a commercial abattoir, the combined application of several antimicrobial interventions would be ideal.